2017
DOI: 10.1177/0887403417742949
|View full text |Cite
|
Sign up to set email alerts
|

Deviant Peer Associations and Perceived Police Legitimacy: Is There a Connection?

Abstract: For police officers to effectively enforce the law, it is imperative that citizens perceive of them as legitimate authority figures. Although procedural justice has shown to be a salient predictor of perceived police legitimacy, a recent line of studies has discovered other significant correlates of this outcome. No study though has explored whether deviant peer associations share a relationship with law enforcement legitimacy evaluations. Questionnaire data were collected from a convenience sample of universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 79 publications
(177 reference statements)
2
20
2
Order By: Relevance
“…Given the link between legitimacy and criminal offending, legitimacy attitudes (or lack thereof) could be considered attitudes conducive to delinquency. Consistent with this argument, examinations of the legal socialization process have found that association with delinquent peers is an important predictor of legitimacy attitudes (Fagan and Tyler 2005; Ferdik, Gist, and Evans 2017; Wolfe et al 2017). Here again, however, this line of research has yet to explore whether changes in delinquent peer associations have different effects on individuals’ legitimacy attitudes over time or whether such peer effects are age-graded and become stronger or weaker in latter stages of the life course.…”
Section: Age-graded Legitimacy Evaluation Developmentmentioning
confidence: 78%
“…Given the link between legitimacy and criminal offending, legitimacy attitudes (or lack thereof) could be considered attitudes conducive to delinquency. Consistent with this argument, examinations of the legal socialization process have found that association with delinquent peers is an important predictor of legitimacy attitudes (Fagan and Tyler 2005; Ferdik, Gist, and Evans 2017; Wolfe et al 2017). Here again, however, this line of research has yet to explore whether changes in delinquent peer associations have different effects on individuals’ legitimacy attitudes over time or whether such peer effects are age-graded and become stronger or weaker in latter stages of the life course.…”
Section: Age-graded Legitimacy Evaluation Developmentmentioning
confidence: 78%
“…Thus, associating with antisocial peers is anticipated to have an adverse effect on their own legal socialization-including the school. The majority of research on the link between associations with antisocial peers and legal socialization looks at the relationship within the context of perceptions of police legitimacy, legitimacy of the law, and perceptions of the criminal justice system (Baz Cores & Fernández-Molina, 2020;Fagan & Tyler, 2005;Ferdik et al, 2019;Fine et al, 2016;McClean et al, 2019;Nivette et al, 2020;Walters, 2019;Wolfe et al, 2017). Most of this research shows that perceptions of peer attitudes are favorable to antisocial behavior or perceptions of peer delinquency are related to perceptions of legal authority figures as less legitimate.…”
Section: The Role Of Peers In Shaping Adolescent Perceptions Of Legal Socializationmentioning
confidence: 99%
“…Adolescence is a particularly important time for legal socialization because it is a period of change in which the influence of peers and friends increases in significance (Steinberg & Monahan, 2007;Steinberg & Morris, 2001). Indeed, research shows that the development of legal socialization attitudes and beliefs about legal authorities are modified by peer and friend associations during adolescence (Fagan & Tyler, 2005) and are important to account for when studying how legal attitudes are learned and developed (Baz Cores & Fernández-Molina, 2020;Ferdik et al, 2019;Fine et al, 2016;McLean et al, 2019;Romain & Hassell, 2014;Walters, 2019;Wolfe et al, 2017). Most of the research on legal socialization shows that peer associations are important in shaping perceptions of the legitimacy of police and the criminal justice system (Baz Cores & Fernández-Molina, 2020;Fine et al, 2016;Ferdik et al, 2019;McLean et al, 2019;Romain & Hassell, 2014;Walters, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations